Leadership skills in primary multipurpose cooperative societies in Ethiopia - R Karunakaran; Roba Huka (Agricultural Economics Research Review, 2023)
Cooperatives are considered as an important institution for uplifting the socioeconomic conditions of their members and local communities. To be successful, the cooperatives need to have dedicated and vibrant leaders. This paper analyses leadership skills of the board of directors of the selected multipurpose cooperatives in Ethiopia. The findings show that majority of the directors have basic leadership skills in project management, information technology, and application of cooperative principles. Most of them are good in professional behaviour, interpersonal relations, governance and motivation. Regression results indicate that skill levels are positively associated with education, experience, training, motivation, participation in social activities, and participation in cooperative management.